Collective escape and supratransmission phenomena in a nonlinear oscillators chain - Mekontchou Foudjio, Michael; Thomas Ndjomatchoua, Frank; Lawrence Gninzanlong, Carlos; Tchawoua, Clément (American Institute of Physics, 2020)
In this study, the collective escape and supratransmission phenomena along a nonlinear chain of coupled particles subjected to a cubic on-site potential are considered. It is shown that the minimum initial on-site amplitude for which there is a collective escape increases with the nonlinear coupling. When the chain is forced at one end by a periodical excitation, the system exhibits supratransmission phenomenon in both lower and upper forbidden bandgaps, and, subsequently, it appears that the driving amplitude threshold for supratransmission in the upper forbidden bandgap frequency decreases with the nonlinear coupling. Depending on the frequency range of the gap frequency, the collective escape and supratransmission can occur simultaneously; otherwise, the supratransmission prevails.